2005
DOI: 10.1007/s11010-005-7576-x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial energy metabolism in ischemic preconditioning and cardioplegia: A metabolic control analysis

Abstract: For both, cardioplegia (CP) and ischemic preconditioning (IP), increased ischemic tolerance with reduction in infarct size is well documented. These cardioprotective effects are related to a limitation of high energy phosphate (HEP) depletion. As CP and IP have to be assumed to act by different mechanisms, their effects on myocardial HEP metabolism cannot be assumed to be identical. Therefore, a systematic analysis of myocardial HEP metabolism for both procedures and their combination was performed, addressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This could contribute protection by reducing ATP hydrolysis after ischemic insults. There have also been reports that PC induces an improved recovery of cardiac ATP levels following prolonged IR injury (10,15,16). This is consistent with the hypothesis that cardiac PC may improve F 1 F 0 -ATP synthase-mode activity as well.…”
Section: Agrklalktidwvsfsupporting
confidence: 84%
See 2 more Smart Citations
“…This could contribute protection by reducing ATP hydrolysis after ischemic insults. There have also been reports that PC induces an improved recovery of cardiac ATP levels following prolonged IR injury (10,15,16). This is consistent with the hypothesis that cardiac PC may improve F 1 F 0 -ATP synthase-mode activity as well.…”
Section: Agrklalktidwvsfsupporting
confidence: 84%
“…It should be noted that four different F 1 F 0 -ATPase preparations, three different PKC preparations, and two different lots of peptides were used to obtain the data shown in Fig. 1, B-D. A major finding of our study was that one of the peptides (NH 2 -2 AGRKLALKTID-WVSF 16 -COOH) demonstrated a dose-dependent inhibition of the PKC␦-dF 1 F 0 binding interaction (Fig. 1B).…”
Section: Design Of Df 1 F 0 -Derived Peptides-our Previous Studies Inmentioning
confidence: 62%
See 1 more Smart Citation
“…At present the preferred protein used for this purpose is cardiac troponin I (cTnI) [4]–[6]. cTnI is a myofibrillar protein which complexes with tropomyosin and troponins T and C to minimize Ca ++ binding to troponin C, and prevent subsequent crossbridge formation between the actin and myosin myofilaments [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proposed that cardiac preconditioning (PC), a cardio-protective response against IR injury, inhibits F 1 Fo ATPase-mode activity [24], [25], which may contribute protection by reducing ATP hydrolysis after ischemic insults. There have also been reports that PC induces an improved recovery of cardiac ATP levels following prolonged IR injury [1], [2], [6]. The F 1 Fo complex therefore, has the potential to impact thousands of energy-requiring processes that contribute to normal cardiac functioning and IR injury.…”
Section: Introductionmentioning
confidence: 99%